2014
DOI: 10.1007/978-4-431-55245-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Water Chemistry of the Middle Amur River

Abstract: This chapter examines water chemistry in terms of iron, organic matter, and nutrients in river, drainage, and groundwater from the middle reaches of the Amur River, to ascertain the watershed environment of the Amur River Basin during 2005-2007. Nitrate-N concentration was 0.46 ± 0.38 mg/L for river water and 1.9 ± 5.0 mg/L for groundwater, corresponding respectively to 87 ± 11 % and 39 ± 42 % of total inorganic nitrogen. Dissolved iron concentrations were 0.10-1.08 mg/L

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…From spring to summer, increases in irradiance and temperature lead to the melting of sea ice, resulting in the formation of a pycnocline in surface waters of the Sea of the Okhotsk. Also impacting the region is the Amur River, the longest river (4350 km) in the far eastern region of Russia, supplying not only large volumes of freshwater (Ogi et al, 2001), but also high levels of nutrients including Fe and organic matter into the Sea of Okhotsk via the southwardflowing East Sakhalin Current which runs along the eastern coast of Sakhalin Island (Nishioka et al, 2007;Andreev and Pavlova, 2009;Nagao et al, 2010;Takao et al, 2014). According to Nagao et al (2010), Amur River water contains ca.…”
mentioning
confidence: 99%
“…From spring to summer, increases in irradiance and temperature lead to the melting of sea ice, resulting in the formation of a pycnocline in surface waters of the Sea of the Okhotsk. Also impacting the region is the Amur River, the longest river (4350 km) in the far eastern region of Russia, supplying not only large volumes of freshwater (Ogi et al, 2001), but also high levels of nutrients including Fe and organic matter into the Sea of Okhotsk via the southwardflowing East Sakhalin Current which runs along the eastern coast of Sakhalin Island (Nishioka et al, 2007;Andreev and Pavlova, 2009;Nagao et al, 2010;Takao et al, 2014). According to Nagao et al (2010), Amur River water contains ca.…”
mentioning
confidence: 99%
“…Organic compounds can also be characterized with SEC-HPLC [ 37 , 38 ]. Six different peaks were detected ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the results of this study indicate that permafrost wetlands ( Mari ) in the Amur‐Mid Basin are important sources of dFe and DOC to rivers in summer. According to monitoring of dFe concentration at several stations along the main stem of the Amur River, dFe flux from the Amur‐Mid Basin to Lower Basin in summer was estimated to be 2.86 × 10 8 g day −1 , which dominates approximately 33% of dFe flux at the station closest to the river mouth (Nagao et al., 2007). Additionally, Levshina (2012) found that the share of Fe‐organic complexes to total dFe concentration in the Bureya River, which is a major tributary in the Amur‐Mid Basin, was higher than those in tributaries in the Amur‐Lower Basin.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that dFe, transported from the Amur‐Mid Basin, is highly stable during the river transport. In recent years, it is generally believed that non‐permafrost wetlands in the Amur‐Lower Basin are source of dFe to the Amur River (Nagao et al., 2007; Pan et al., 2011; Wang et al., 2012). To this understanding, this study proposes for the first time that permafrost wetlands ( Mari ) in the Amur‐Mid Basin are also important source of dFe to the Amur River and perhaps to the Sea of Okhotsk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation